1995
DOI: 10.1128/aac.39.12.2749
|View full text |Cite
|
Sign up to set email alerts
|

Open-label crossover study to determine pharmacokinetics and penetration of two dose regimens of levofloxacin into inflammatory fluid

Abstract: Two levofloxacin administration regimens were used for six healthy male volunteers. They received either 500 mg of levofloxacin orally every 12 h for five doses or 500 mg every 24 h for three doses, and then 6 weeks later they received the other course. The concentrations of the drug in plasma, cantharidin-induced inflammatory fluid, and urine were measured with a microbiological assay following administration of the final dose. Mean peak concentrations in plasma of 9.3 and 6.6 g/ml were attained 1.1 and 1.2 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 11 publications
3
30
0
Order By: Relevance
“…Our results for 24 HIV-infected patients indicated that the systemic exposure to levofloxacin, when combined with NFV or with EFV, is not different from that previously observed in this population, when patients were not receiving these two antiretroviral agents (2, 6), or in healthy volunteers (3)(4)(5)(6)12). The longer levofloxacin T max observed in our patients taking EFV (3.3 h), if compared with the NFV group (1.4 h) or with historical controls (range, 0.9 to 1.7 h), may be referable to the delayed gastric-emptying phenomenon observed in a recent study of animals receiving EFV (1).…”
Section: Subject Groupsupporting
confidence: 51%
See 1 more Smart Citation
“…Our results for 24 HIV-infected patients indicated that the systemic exposure to levofloxacin, when combined with NFV or with EFV, is not different from that previously observed in this population, when patients were not receiving these two antiretroviral agents (2, 6), or in healthy volunteers (3)(4)(5)(6)12). The longer levofloxacin T max observed in our patients taking EFV (3.3 h), if compared with the NFV group (1.4 h) or with historical controls (range, 0.9 to 1.7 h), may be referable to the delayed gastric-emptying phenomenon observed in a recent study of animals receiving EFV (1).…”
Section: Subject Groupsupporting
confidence: 51%
“…The pharmacokinetics (PK) of levofloxacin following single and multiple oral and intravenous doses have been widely studied (3)(4)(5)12; M. L. Holland, S. C. Chien, M. L. Corrado, et al, 5th Int. Symp.…”
mentioning
confidence: 99%
“…The main features and general operation of the system and the method for preparing standardized inocula for the experiments have been described previously (4). Log-phase cultures (ϳ10 7 CFU/ml) were exposed to a series of monoexponential levofloxacin pharmacokinetic profiles for 96 h. Three simulations were designed to reproduce the concentration-time profiles of clinical levofloxacin doses of 750 mg, 500 mg, and 250 mg administered as intermittent 1-hour infusions every 24 h. The simulated central and peripheral compartment concentrations were intended to mimic the total levofloxacin concentrations observed in plasma and skin blister fluid, respectively, of adult patients with normal renal function (6)(7)(8)(9)). An additional experimental regimen (125 mg every 24 h) was simulated to produce levofloxacin concentrations below the MPCs of the study strains for the entire duration of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Several observations would suggest that intrapulmonary concentrations of both drugs would be higher in patients with clinical conditions of inflammation and/or infection than in healthy volunteers. First, levofloxacin and azithromycin achieve high concentrations in the inflammatory infection model of blister fluid (9,18). Azithromycin and fluoroquinolones have displayed extensive accumulation by phagocytes which may allow further drug delivery at sites of infections (6,37).…”
Section: Fig 2 (A To C)mentioning
confidence: 99%